Expanding the molecular landscape of childhood apraxia of speech: evidence from a single-center experience - Formicola, Daniela; Podda, Irina; Dirupo, Elia; Andreucci, Elena; Giglio, Sabrina; Cipriani, Paola; Bombonato, Clara; Santorelli, Filippo Maria; Chilosi, Anna (Frontiers in Neuroscience, 2024)
BackgroundChildhood apraxia of speech (CAS) is a genetically heterogeneous pediatric motor speech disorder. The advent of whole exome sequencing (WES) and whole genome sequencing techniques has led to increased identification of pathogenic variants in CAS genes. In an as yet uncharacterized Italian cohort, we aimed both to identify new pathogenic gene variants associated with CAS, and to confirm the disease-related role of genes already reported by others. We also set out to refine the clinical and neurodevelopmental characterization of affected children, with the aim of identifying specific, gene-related phenotypes.MethodsIn a single-center study aiming to explore the genetic etiology of CAS in a cohort of 69 Italian children, WES was performed in the families of the 34 children found to have no copy number variants. Each of these families had only one child affected by CAS.ResultsHigh-confidence (HC) gene variants were identified in 7/34 probands, in two of whom they affected KAT6A and CREBBP, thus confirming the involvement of these genes in speech impairment. The other probands carried variants in low-confidence (LC) genes, and 20 of these variants occurred in genes not previously reported as associated with CAS. UBA6, ZFHX4, and KAT6A genes were found to be more enriched in the CAS cohort compared to control individuals. Our results also showed that most HC genes are involved in epigenetic mechanisms and are expressed in brain regions linked to language acquisition processes.ConclusionOur findings confirm a relatively high diagnostic yield in Italian patients.